Histological Follow-Up in Patients with Atypical Glandular Cells on Pap Smears - Boyraz, Gokhan; Basaran, Derman; Salman, Mehmet Coskun; Ibrahimov, Akbar; Onder, Sevgen; Akman, Orkun; Ozgul, Nejat; Yuce, Kunter (Medknow Publications & Media Pvt Ltd, 2017)
CONTEXT: Atypical glandular cells (AGCs) result in the Papanicolaou (Pap) smear may be associated with significant genital and nongenital neoplastic processes. AIMS: To evaluate the underlying histopathology in women who had AGCs on Pap smears. SETTINGS AND DESIGN: Retrospective cross-sectional study. PATIENTS AND METHODS: Clinicopathological data of patients who had AGC on Pap smears and underwent histological workup between January 2004 and December 2014 were retrieved from the computerized database of a tertiary care center. Patients with a prior history of cervical intraepithelial neoplasia or gynecological cancer were excluded. STATISTICAL ANALYSIS USED: Chi-square test or Fisher's exact tests were used as appropriate. RESULTS: Cytological examination of the uterine cervix was carried out in 117,560 patients. We identified 107 patients (0.09%) with AGC and 80 of those with histological follow-up were included in the study. The median age at diagnosis was 47 years (range, 18–79), and 32 women (40%) were postmenopausal, while 56 (70%) had gynecological symptoms. Significant preinvasive or invasive lesions on pathological examination were detected in 27 (33.8%) patients, including 12 endometrial adenocarcinomas (15%), 8 cervical carcinomas (10%), 3 cervical intraepithelial neoplasia II/III (3.75%), 2 ovarian adenocarcinomas (2.5%), and 2 metastatic tumors (2.5%). Univariate analysis showed that postmenopausal status (P < 0.001), age >50 years old (P < 0.001), having symptoms at the time of admission (P = 0.041), and AGC “favor neoplasia” smear results (P = 0.041) were the clinical factors associated with significant pathological outcome. CONCLUSIONS: Patients with AGC on Pap smears should be evaluated vigilantly with histological workup, especially if they are postmenopausal or symptomatic.